1955
DOI: 10.1111/j.1365-2621.1955.tb16804.x
|View full text |Cite
|
Sign up to set email alerts
|

A SIMPLIFIED MEDIUM FOR COUNTING CLOSTRIDIUM SPORESab

Abstract: J. Buc~., 62, 425-432 (1951). 21-25 (1950).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

1956
1956
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 3 publications
1
23
0
Order By: Relevance
“…; samples were withdrawn at intervals, rapidly cooled in ice and stored in the refrigerator. Spore viability was determined by colony counts in oval culture tubes using the medium of Wynne, Schmieding & Daye (1955) solidified with 1-5 % agar.…”
Section: N G R E C Z and T T A N G Methodsmentioning
confidence: 99%
“…; samples were withdrawn at intervals, rapidly cooled in ice and stored in the refrigerator. Spore viability was determined by colony counts in oval culture tubes using the medium of Wynne, Schmieding & Daye (1955) solidified with 1-5 % agar.…”
Section: N G R E C Z and T T A N G Methodsmentioning
confidence: 99%
“…Culture Colony count/ml in medium containing: With the object of suppressing a t least some lactobacilli, a trial was then made of the anaerobic medium developed by Wynne, Schmieding t Daye (1955), which contains only yeast extract as a source of organic nutrients and is therefore even poorer than another, older American medium, that of Reynolds et al (1952) which had no liver extract but did contain tryptone and yeast extract. Nevertheless it was confirmed that Wynne's medium is as suitable for clostridia as standard, rich anaerobic media (Frank & Campbell, 1955).…”
Section: Comparison Of Two Redox Potential Poising Agents In Tryptmentioning
confidence: 99%
“…Sodium bicarbonate, known to improve recovery of Clostridium species (Wynne et al, 1955), markedly improved the recovery rate of heat activated and heat stressed PA3679 spores when it was included in MPA3679A. Like lysozyme, sodium bicarbonate was found to depress the recovery of heat-stressed spores when used in quantities greater than 0.1%.…”
Section: Resultsmentioning
confidence: 96%
“…The medium recommended to confirm NFPA's spore counts was Andersen's Pork Pea Infusion (APPI) using the Most Probable Number (MPN) technique (Andersen, 195 1;Bernard, 1983). As alternatives to APPI and the MPN method, several anaerobic plating media have been developed for enumeration of PA3679 spores (Wynne et al, 1955;Polvino and Bernard, 1982;Frank and Campbell, 1955;Hauschild and Hilsheimer, 1977;Pflug et al, 1979;Wheaton and Pratt, ,196l;Andersen, 1951;Odlaug and Pflug, 1977). Improvement in subculture methods and especially improvement in the subculture medium for recovering injured spores from inoculated pack tests would increase the accuracy of establishing a safe process.…”
Section: Introductionmentioning
confidence: 99%